O PAI, A MÃE E O DISCURSO PUBLICITÁRIO: ENTRE A PROFUSÃO E O INTERDITO - Cattelan, João Carlos (Revista Literatura em Debate, 2015)
O PAI, A MÃE E O DISCURSO PUBLICITÁRIO: ENTRE A PROFUSÃO E O INTERDITO